Teachers’ Attitudes towards Student Caning: Do Differences in Socio-demographic Characteristics Really Matter? (Journal of Humanities & Social Science (JHSS), 2021)
Research findings from low-income and high-income countries indicate that teachers’ use of violent discipline is prevalent. However, studies that explore teachers’ attitudes towards violence and its association to their socio-demographic characteristics are lacking. This paper assessed teachers’ attitudes towards student caning and the associated teachers’socio-demographic characteristics. The data were drawn from four schools in two regions using a case study design. Considering the total number of participants, 72 teachers (53% females; average age: 32.47 years, SD = 6.64, range: 22–59 years) participated in this study. Of the 72 teachers, their qualification ranged from postgraduate degree (2.8%), bachelor’sdegree (74%), two year diploma in education (21%), and others (2.8%). Furthermore, 54% (n = 39) of the teachers were from rural school settings. The findings indicate that teachersin the study have positive attitudes towards student caning. However, their differences in socio-demographic characteristics did not show any difference in their attitudes towards student caning. This implies that other factors such as culture and parenting orientations might be responsible for the reported attitude. Hence, interventions on attitude change are recommended to reverse the current teachers’ positive attitudes towards caning as a means of discipline management in schools.